On normalizers in fuzzy groups - Kurdachenko, L.A.; Grin, K.O.; Turbay, N.A. (Algebra and Discrete Mathematics, 2013)
In an arbitrary fuzzy group we define the normalizer of fuzzy subgroup and study some its properties. In particular, the characterization of nilpotent fuzzy group has been obtained.